2013
DOI: 10.5114/wo.2013.35280
|View full text |Cite
|
Sign up to set email alerts
|

Main influencing factors and health-related quality of life issues in patients with oesophago-gastric cancer – as measured by EORTC tools

Abstract: Aim of the studyTo assess influencing factors and main health-related quality of life (HRQoL) issues in patients with cancers of the oesophago-gastric region using the European Organization for Research and Treatment of Cancer (EORTC) quality of life questionnaire Core 30 (QLQ-C30) and its oesophago-gastric module (QLQ-OG25).Material and methodsPatients were qualified for this study based on the histological confirmation of oesophageal, oesophago-gastric or gastric cancers. Each patient filled out the Polish v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 21 publications
3
8
0
Order By: Relevance
“…However, the authors considered that this symptom seemed to be physiologically unrelated to postoperative complications 14 . Insomnia was also considered more as psychological issues than physiological ones 40 . This may be one of the reasons why the scores of insomnia item fluctuated.…”
Section: Discussionmentioning
confidence: 99%
“…However, the authors considered that this symptom seemed to be physiologically unrelated to postoperative complications 14 . Insomnia was also considered more as psychological issues than physiological ones 40 . This may be one of the reasons why the scores of insomnia item fluctuated.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly noteworthy are the associations with socio-demographic factors that can be observed across almost all domains. While the association with age and gender is observed in almost all HRQoL studies [33], the positive correlation between HRQoL and early retirement/old age pension is not a general finding in oncology [34,35]. It seems possible that with the removal of occupational demands, mental and physical capacities are released, which ultimately has a positive effect on HRQoL.…”
Section: Results In Contextmentioning
confidence: 97%
“…Elder patients were more likely to report problems in the pain/discomfort dimension. Tomaszewski et al reported that oesophagogastric cancer patients aged ≥60 years had higher pain and discomfort scores than patients aged <60 years . In general, the HRQoL of elder patients is always significantly lower owing to the decline in physical function and the poor endurance capacity.…”
Section: Discussionmentioning
confidence: 99%